Barriers to clinical learning skills development among midwifery students and newly qualified midwives in Morocco: A qualitative study - Mramel, Majida; El Alaoui, Mustafa; El Janati Idrissi, Rachid (Belitung Raya Foundation, Indonesia, 2024)
Background: In Morocco, despite various initiatives to improve the quality of reproductive healthcare, the indicators remain unfavorable. To strengthen the skills of midwives and support the achievement of Millennium Development Goals (MDGs) 4 and 5 by 2030, Morocco has developed and implemented a competency-based training framework. However, there is a lack of information on the successful implementation of this program and its impact on the quality of student midwives’ preparation for practice. Objective: This study aimed to gain a deeper understanding and explore the barriers affecting the development of clinical learning skills among midwifery students and newly qualified midwives. Methods: This study employed a descriptive, exploratory qualitative approach. Data were collected through nine focus group discussions with 30 midwifery students and 24 newly graduated midwives between April and June 2023 from six higher education institutions in northern and central Morocco. Inductive content analysis was used to analyze the transcribed discussions. Results: The barriers varied between locations. Overall, the internship design was inadequate, and the clinical environment was insufficient. Participants highlighted limited opportunities to experience the full range of midwifery skills. However, most midwifery students and new graduates had deficient competencies in managing high-risk situations and emergencies. Conclusion: This work provides an overview of the nature and extent of the challenges faced by many student midwives in Morocco, resulting in newly graduated midwives being poorly prepared for the full range of midwifery practice. These findings can inform various initiatives to strengthen midwifery education at the global, regional, and national levels.